Enhancing Livelihood Security via Mushroom Production: A Case Study of technological Support and farmers’ ingenuity - acharya, Sumita (International Journal of Social Science, 2024)
Mushrooms, a diverse and vital organism, offer an economical and eco-friendly solution for utilizing agricultural and forest wastes, presenting substantial potential for sustainable farming globally. This study employed a case study approach to evaluate technological interventions in mushroom cultivation among 40 mushroom growers in Puri district over three years. Practices compared included using crumpled straw soaked with 2% calcium carbonate for paddy straw mushrooms, humidity management with fogger, and cultivating blue oyster mushrooms. Results indicated significant improvements in yield, biological efficiency, and economic returns, demonstrating the effectiveness of these interventions. Focusing on Mr. Laxman Bastia, an innovative farmer from Puri district, the study also highlighted his adoption of advanced mushroom cultivation techniques with support from KVK Puri. By implementing these interventions in mushroom cultivation, Mr. Bastia significantly increased yields, reduced costs, and enhanced profitability. His innovations, including a spawn bottle-carrying trolley, fuel-saving chulla, and wheat cleaner, further improved efficiency and reduced labor dependency. These efforts earned him widespread recognition, including the "Progressive Mushroom Grower Award" by ICAR. Mr. Bastia's success underscored the potential of mushroom cultivation to boost productivity, profitability, and nutritional security, offering a viable livelihood option for farm families. His enterprise achieved an impressive annual turnover of ₹ 63,82,000/-, creating year-round employment for five individuals and part-time opportunities for Women Self-Help Group members. The study highlighted the importance of training, technological support, and innovative practices in advancing mushroom entrepreneurship, particularly among farm-women and rural youths. Future strategies aim to strengthen market connections and promote value-added mushroom products, ensuring continued growth and sustainability in the mushroom industry.